2002
DOI: 10.1021/ol026988e
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Modulated Palladium Oxidation Catalysis:  Mechanistic Insights into Aerobic Alcohol Oxidation with the Pd(OAc)2/Pyridine Catalyst System

Abstract: Pd(OAc)(2):pyridine (1:4) is an efficient catalyst system for the oxidation of alcohols with molecular oxygen. A mechanistic study of this reaction reveals that pyridine promotes the aerobic oxidation of palladium(0) but inhibits the oxidation of alcohol by palladium(II). Kinetic results reveal that turnover-limiting substrate oxidation consists of (i) formation of a palladium(II)-alkoxide, (ii) pyridine dissociation, and (iii) beta-hydride elimination. These results provide a framework for the design and/or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(88 citation statements)
references
References 22 publications
5
79
1
3
Order By: Relevance
“…Detailed kinetic investigations, alongside in situ [8], [9] and [10] and operando studies [11], [12], [13] and [14] have provided conclusive evidence that allylic alcohol oxidation occurs via a redox mechanism, catalysed by electron deficient, surface Pd(II) species present as PdO. Kumar et al [15], Scott et al [16] and Hara et al [17] have likewise reported a heterogeneous Pd(II) active species responsible for aerobic alcohol selox, while homogeneous Pd(II) complexes are well known to catalyse such alcohol oxidations [18], [19] and [20]. Interestingly, surface PtO2 has also been recently reported as the active phase in the analogous Pt catalysed aerobic selox of allylic alcohols [21].…”
Section: Introductionmentioning
confidence: 97%
“…Detailed kinetic investigations, alongside in situ [8], [9] and [10] and operando studies [11], [12], [13] and [14] have provided conclusive evidence that allylic alcohol oxidation occurs via a redox mechanism, catalysed by electron deficient, surface Pd(II) species present as PdO. Kumar et al [15], Scott et al [16] and Hara et al [17] have likewise reported a heterogeneous Pd(II) active species responsible for aerobic alcohol selox, while homogeneous Pd(II) complexes are well known to catalyse such alcohol oxidations [18], [19] and [20]. Interestingly, surface PtO2 has also been recently reported as the active phase in the analogous Pt catalysed aerobic selox of allylic alcohols [21].…”
Section: Introductionmentioning
confidence: 97%
“…As discussed in the introduction, alcohols are often used as solvents in reactions catalyzed by Pdbased catalysts [33], or they may be used even as reactants [34][35][36][37][38][39][40][41]. Therefore, it is important to clarify if they are innocent toward the catalyst, or if they may react with it and eventually lead to its final deactivation.…”
Section: Thermal Behavior Of P4vp/pd(oac)2 In Presence Of Alcohols: Imentioning
confidence: 99%
“…In other cases, alcohols are used as reactants. For example, alcohol hydrogenation, oxidation and cross-coupling reactions are also catalyzed by palladium-based catalysts, either homogeneous or heterogeneous [34][35][36][37][38][39][40][41]. In this respect, the homogeneous Pd(OAc)2/pyridine system is by far one of the most efficient and selective catalyst for oxidation of alcohols to aldehydes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations